Perbandingan Efektivitas Isometric Quadriceps Exercise dan Aquatic Exercise Terhadap Tingkat Nyeri pada Lansia dengan Knee Oteoarthritis : Literature Review - Bestari, Dt.Arief Rahman; Yuliadarwati, Nungki Marlian; Utami, Kurnia Putri (UI Scholars Hub, 2022)
The elderly are the most susceptible subject to knee osteoarthritis (KOA), there are several good exercises for KOA, namely isometry quariceps exercise (IQE) and Aquatic exercise (AQE) are therapies that are often used to help improve and reduce pain in KOA. To compare the effectiveness of giving isometric quadriceps exercise and aquatic exercise on pain levels in the elderly with knee osteoarthritis. This study is a literature review where researchers will look for journals that match the theme and title to be discussed. articles or journals are obtained from several search engines, Pubmed and Google Scholar. The journal criteria used in this study are articles published in 2016 – 2021 as many as 9 journals with 8 journals for international articles and 1 for national journals. After analyzing the international and national journals/articles, this study obtained the average significance value of each journal, namely IQE 0.0036 and AQE 0.030. IQE is more effective than AQE in terms of reducing COA pain in the elderly with the VAS and WOMAC measurement instruments.